The Context of StichTrial: Viable or not viable Does it matter before revascularization? - Ahmed, Chaudhury Meshkat; Sultan, Md Ashraf Uddin (University Heart Journal, 2021)
Abstract not available University Heart Journal Vol. 17, No. 2, Jul 2021; 79-80